Multi-scale gyrokinetic simulations of an Alcator C-Mod, ELM-y H-mode plasma. (7th November 2017) - Howard, N T; Holland, C; White, A E; Greenwald, M; Rodriguez-Fernandez, P; Candy, J; Creely, A J
Abstract: High fidelity, multi-scale gyrokinetic simulations capable of capturing both ion ( k θ ρ s ∼  ( 1.0 ) ) and electron-scale ( k θ ρ e ∼  ( 1.0 ) ) turbulence were performed in the core of an Alcator C-Mod ELM-y H-mode discharge which exhibits reactor-relevant characteristics. These simulations, performed with all experimental inputs and realistic ion to electron mass ratio ( ( m i / m e ) 1 / 2 = 60.0 ) provide insight into the physics fidelity that may be needed for accurate simulation of the core of fusion reactor discharges. Three multi-scale simulations and series of separate ion and electron-scale simulations performed using the GYRO code (Candy and Waltz 2003 J. Comput. Phys. 186 545) are presented. As with earlier multi-scale results in L-mode conditions (Howard et al 2016 Nucl. Fusion 56 014004), both ion and multi-scale simulations results are compared with experimentally inferred ion and electron heat fluxes, as well as the measured values of electron incremental thermal diffusivities—indicative of the experimental electron temperature profile stiffness. Consistent with the L-mode results, cross-scale coupling is found to play an important role in the simulation of these H-mode conditions. Extremely stiff ion-scale transport is observed in these high-performance conditions which is shown to likely play and important role in the reproduction of measurements of perturbative transport. These results provide important insight into the role of multi-scale plasma turbulence in the core of reactor-relevant plasmas and establish important constraints on the the fidelity of models needed for predictive simulations.